Assessing the Cost-Utility of Universal Hepatitis B Vaccination Among Adults . (9th March 2022) - Hall, Eric W; Weng, Mark K; Harris, Aaron M; Schillie, Sarah; Nelson, Noele P; Ortega-Sanchez, Ismael R; Rosenthal, Elizabeth; Sullivan, Patrick S; Lopman, Ben; Jones, Jeb; Bradley, Heather; Rosenberg, Eli S
Abstract: Background: Although effective against hepatitis B virus (HBV) infection, hepatitis B (HepB) vaccination is only recommended for infants, children, and adults at higher risk. We conducted an economic evaluation of universal HepB vaccination among US adults. Methods: Using a decision analytic model with Markov disease progression, we compared current vaccination recommendations (baseline) with either 3-dose or 2-dose universal HepB vaccination (intervention strategies). In simulated modeling of 1 million adults distributed by age and risk groups, we quantified health benefits (quality-adjusted life years, QALYs) and costs for each strategy. Multivariable probabilistic sensitivity analyses identified key inputs. All costs reported in 2019 US dollars. Results: With incremental base-case vaccination coverage up to 50% among persons at lower risk and 0% increment among persons at higher risk, each of 2 intervention strategies averted nearly one-quarter of acute HBV infections (3-dose strategy, 24.8%; 2-dose strategy, 24.6%). Societal incremental cost per QALY gained of 152 722 (interquartile range, 119 113–235 086) and 155 429 (interquartile range, 120 302–242 226) were estimated for 3-dose and 2-dose strategies, respectively. Risk of acute HBV infection showed the strongest influence. Conclusions: Universal adult vaccination against HBV may be an appropriate strategy for reducing HBV incidence and improving resulting health outcomes. Abstract : Implementation of risk-based hepatitis B vaccination among adults has been suboptimal. We present an economic evaluation of universal hepatitis B vaccination that informed a revision to the Advisory Committee on Immunization Practices adult hepatitis B vaccination recommendations.